Nutrition guidelines for strength sports: Sprinting, weightlifting, throwing events, and bodybuilding - Slater, G.; Phillips, S. M. (Journal of Sports Sciences, 2011)
Strength and power athletes are primarily interested in enhancing power relative to body weight and thus almost all undertake some form of resistance training. While athletes may periodically attempt to promote skeletal muscle hypertrophy, key nutritional issues are broader than those pertinent to hypertrophy and include an appreciation of the sports supplement industry, the strategic timing of nutrient intake to maximize fuelling and recovery objectives, plus achievement of pre-competition body mass requirements. Total energy and macronutrient intakes of strength-power athletes are generally high but intakes tend to be unremarkable when expressed relative to body mass. Greater insight into optimization of dietary intake to achieve nutrition-related goals would be achieved from assessment of nutrient distribution over the day, especially intake before, during, and after exercise. This information is not readily available on strength-power athletes and research is warranted. There is a general void of scientific investigation relating specifically to this unique group of athletes. Until this is resolved, sports nutrition recommendations for strength-power athletes should be directed at the individual athlete, focusing on their specific nutrition-related goals, with an emphasis on the nutritional support of training.